A abordagem sociolinguística para a estrutura narrativa dos romances Segredo de Pedra e A Maldição do Padre, de Ivo Gasparin - MORAIS, MAURI DA CRUZ DE (2021)
The southern region of Brazil has a wide cultural and linguistic variety. Several factors contribute to this, among which the following stand out: (a) it is a border region with Spanish-speaking countries; (b) it was initially disputed land by the Portuguese and Span iards, and the Portuguese took possession of it definitively only from the 17th and 18th centuries; (c) large waves of European immigrants, mainly Italians and Germans, speakers of languages other than Portuguese, were established in the region from the 19th century onwards. Among the European groups in contact with the Portuguese, Italian assumes a prominent position. Talian, a language formed in Brazil, is also recognized in 2014 as a Brazilian Cultural Reference, along with the indigenous languages, Asurini do Trocará and Guarani Mbya, inventoried in 2010, being were the first to be recognized by IPHAN and the Ministry of Culture, MinC. On November 19, 2014, these languages became part of the National Inventory of Linguistic Diversity (NILD), according to Decree 7387/2010. In an attempt to strengthen the Talian Culture, we dedicated ourselves to the study of interfaces between sociolinguistics and literature, from the works “Segredo de Pedra” and “A Maldição do Padre” by Ivo Gasparin, in which we analyzed the variation of the tonic nasal diphthong -ão in Portuguese, noting Talian marks that correspond to the alternation -ão > -on in words like pão (bread) -pon, então (then) -inton, for example. We look for theoretical support in sociolinguistics: Weinreich, Labov and Herzog, 2006; Labov, 2008, 1994, 2001; Linguistic diversity of RS, 2018; Luzzatto, Maestri, 1998; Bagno, 2015. We also draw on studies between sociolinguistics and literature, by Preti (1974), in which we seek to explain, through the theory of sociolinguistics, the re gionalism that is very present in modernist works, based on a regionalist model which the writer applies to reinforce the nationality instinct and the project of preservation of the Talian. The process of linguistic contact assumes greater importance when younger people realize that their way of speaking is the basis of a critical linguistic prejudice, which has roots in Getúlio Vargas’s Nationalization Project, in which the idea of a “pure nation” persisted, which aimed to “whiten” the country, seeking workers from Europe and who, upon entering Brazil, were silenced and prohibited from speaking the only language they knew, due to the mandatory and exclusive use of the Portuguese language. The occur rences of the diphthong –ão, -on are due to the inexistence of the nasal -ão in Talian.